Perkembangan Fisik dan Kognitif pada Masa Kanak-Kanak Pertengahan - Nurmawaty Hasugian; Khairunissa Khairunissa; Dilla Bunaiya; Riswan Pasaribu (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Physical and cognitive development in middle childhood undergoes many significant changes. Children at this age develop problem-solving skills, abstract thinking, and language development in cognitive aspects. They have the ability to understand the concepts of time and space, as well as improve their reading and writing skills. At this stage, physical development includes rapid body growth, muscle strengthening, and improved motor coordination. Children usually experience rapid height growth and organ development. Physical activities and activities involving movement are becoming increasingly important for achieving an optimal level of physical fitness. These two components are interrelated, and good physical health can support cognitive development. Positive simulations, environmental factors, and education also played an important role in shaping the holistic development of the time.